2004
DOI: 10.3348/kjr.2004.5.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Transvaginal Ultrasonography with Hysterosonography as a Screening Method in Patients with Abnormal Uterine Bleeding

Abstract: ObjectiveTo assess the utility of hysterosonography (HS) as a screening method in patients with abnormal uterine bleeding.Materials and MethodsWe retrospectively reviewed transvaginal ultrasonography (TVS) and HS for 105 patients whose diagnosis was confirmed pathologically. All 105 patients were initially evaluated on the same day with both TVS and HS. On TVS and HS examination, endometrial cavitary lesions were classified as diffuse hyperplasia, endometrial polyp, endometrial cancer, uterine synechia and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 13 publications
4
30
0
1
Order By: Relevance
“…Few studies published so far indicated that SIS may have some advantages as compared to the TVS in differentiating diffuse mass but there is no clear advantage observed and more exploration is needed in this area. [4][5][6] The study was designed with the aim of comparison of SIS and TVS for detecting intracavitary abnormalities in women with abnormal uterine bleeding, using the final diagnosis, established at hysterectomy as reference.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies published so far indicated that SIS may have some advantages as compared to the TVS in differentiating diffuse mass but there is no clear advantage observed and more exploration is needed in this area. [4][5][6] The study was designed with the aim of comparison of SIS and TVS for detecting intracavitary abnormalities in women with abnormal uterine bleeding, using the final diagnosis, established at hysterectomy as reference.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity and specificity of SIS have been reported to be as high as 85-91% and 83-100%, respectively. (3,9,11,14) Our result have shown 0.96% Sensitivity, 0.90% Specificity, 0.96% PPV, and 0.90% NPV for SIS to diagnose intracavitary/endometrial lesions. Similar high accuracy rates ranging from 84% to 96% have been reported by other studies.…”
Section: Discussionmentioning
confidence: 75%
“…Several studies in recent literature have indicated that saline infusion sonography can differentiate intracavitary masses from more diffuse endometrial thickening. (6)(7)(8)(9)(10)(11) This study was performed to evaluate the role of SIS in detecting the endometrial lesion in women with AUB and thickened endometrium. Although, the use of fluid enhancement in abdominal ultrasound was described both for uterine and tubal observations.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33] It consists of irregularly heaped-up tissue with a granular or at times necrotic appearance. It appears opaque, dry, pale yellow or white and friable.…”
Section: Dsjuogmentioning
confidence: 99%